Problem-based blended learning: The student's critical thinking skills in the respiratory system - Jannah, Na'imatul; Saifuddin, Much Fuad (Universitas Negeri Jakarta, 2024)
Critical thinking skills should be integrated into high school biology education through problem-based blended learning.. This study aims to determine the effect of the Problem-Based blended learning model on students' critical thinking skills in the material on the respiratory system at SMA A. This quasi-experimental study used a nonrandomized control group, pretest-posttest design involving 2 XI classes, namely the control class, which consisted of 33 students and 32 students in the experimental class. Collecting data on critical thinking skills is using a test technique. The test instrument used is a question sheet (pretest and posttest). The data analysis consisted of analysis prerequisites in the form of a normality test and homogeneity test, as well as hypothesis testing in the form of the Mann-Whitney test. This study's results indicate a significant influence on students' critical thinking skills in the respiratory system material for class XI at SMA A after applying the Problem-Based blended learning model assisted by Google Classroom. This can be seen from the average test of critical thinking skills in the experimental class, which is higher than the control class.